Christology, soteriology, and ethics in John and Hebrews collected essays - Loader, William R. G. 1944-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
"This volume brings together essays on John and Hebrews by William R.G. Loader. Beside his monographs on John and Hebrews are numerous contributions to journals, conference volumes, and Festschriften, of which a representative selection is gathered here into a single volume. They discuss how these writings portray Jesus and his significance and deal with continuity and discontinuity with Israel's tradition, as well as address the ethical issues which these texts raise and also evoke."--
Literaturverzeichnis: Seite 383-407
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Person and offices; Jésus-Christ - Personne et fonctions; Jesus Christ; Bible; Bible; Bible; Bible; Salvation -- Christianity; Ethics in the Bible; Son of God; Son of Man; Salut - Christianisme; Morale dans la Bible; Fils de Dieu; Fils de l'homme; Christology; Ethics in the Bible; Salvation - Christianity; Son of God; Son of Man; Aufsatzsammlung